PROFIL SENYAWA DAN AKTIVITAS ANTIOKSIDAN EKSTRAK DAUN SEPAT (Mitragynaspeciosa) DAN DAUN DADANGKAK (Hydrolea spinosa L.) - Rakhmadhan Niah; Eka Kumalasari (Sekolah Tinggi Ilmu Kesehatan ISFI Banjarmasin, 2019)
Sepat folium (Mitragynaspeciosa) and dadangkak folium (Hydrolea spinosa L.) are plants in South Kalimantan. These plants are often used traditionally to reduce blood sugar and antibacterial levels. The effectiveness is suspected because there is strong antioxidant activity in flavonoid compounds. Flavonoid compounds work through the mechanism of capturing free radicals, reducing oxidative stress. The purpose of this study was to determine the profile of flavonoid compounds of sepat folium and dadangkak folium by test the antioxidant activity with DPPH (1,1-diphenyl-2picrylhydrazyl) method. Extract of sepat folium and dadangkak folium were made by the maceration method using methanol as a solvent. Profiles of flavonoid compounds were obtained quantitatively by the standard solution of quercetin. The extract obtained was tested for antioxidant activity by the DPPH (1,1-diphenyl-2picrylhydrazyl) method. The results showed that the total flavonoid value in methanol solvent was the extract of dadakak folium is 51.19 mg QE / g extract and extract of sepat folium is 43.25 mg QE / g extract. Very strong antioxidant activity (<50 Î¼g / mL) was found in methanol extracts of sepat folium with a value of 34.70 Î¼g / mL and methanol extracts of dadangkak folium with a value of 38.41 Î¼g / mL.